ARTIFICIAL INTELLIGENCE IN SUSTAINABLE AGRICULTURE: OPTIMIZING WATER USE IN THE CONTEXT OF CLIMATE CHANGE - Ugrinov, Dragan; Nikolic, Magdalena; Grujičić, Željko; Pažun, Brankica; Langović, Zlatko (Economics of Agriculture, 2026)
This paper examines the application of artificial intelligence (AI) in organic agriculture using the Analytic Hierarchy Process (AHP). A multi-criteria analysis evaluated four key criteria: AI use in optimization, factors affecting precision irrigation, benefits of AI application, and implementation challenges, alongside three alternatives: price, personnel, and terrain. Results show that “implementation problems and challenges” are the most significant criterion (39.52%), while “personnel” is the most important alternative (63.45%), emphasizing the crucial role of human resources in adopting technological solutions. The study also demonstrates high consistency (CR = 0.0274), confirming the reliability of the findings. The paper highlights the need for institutional support, educational programs, improved water resource management, and affordable AI solutions, particularly for small farmers, while proposing directions for future research and policies to advance sustainable agriculture.